Forecasting technological needs and prioritizing factors in agriculture from a plant breeding and genetics domain perspective: A review - V, RAMASUBRAMANIAN; KUMAR, AMRENDER; PRABHU, K V; BHATIA, V K; RAMASUNDARAM, P (The Indian Journal of Agricultural Sciences, 2014)
Future technologies in the domain of Indian agriculture are expected to be different from what these are now. The subject of Technology Forecasting (TF) can be resorted to identify the needs to fill the gaps in the present technological trends. As a TF exercise, Brainstorming and Questionnaire approaches were employed to envision future technological needs for one of the subdomains of agriculture, i e Plant Breeding and Genetics (PB&G). Information obtained from experts was subjected to linear combination weighted scoring method for prioritizing key factors leading to future technological needs and were analyzed using multi-dimensional scaling for identifying key agricultural dimensions.